2000
DOI: 10.1080/01140671.2000.9514143
|View full text |Cite
|
Sign up to set email alerts
|

Irrigation, sawdust mulch, and Enhance®biocide affects soft rot incidence, and flower and tuber production of calla

Abstract: The incidence and severity of soft rot, flower grades, and tuber yields of calla (Zantedeschia spp.) plants were affected by the quantity of water received during the growing season, sawdust mulch, and Enhance ® biocide applications to tubers before planting. Incidence of plants with soft rot symptoms increased at a relatively constant rate during the season reaching an average for all treatments of 61% at the end of flowering. Irrigated plus mulched callas had 15% less soft rot than the irrigation without mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 8 publications
1
19
0
Order By: Relevance
“…In addition, Wright and Burge (2000) observed that symptoms of water stress include lower growth, what is much apparent in this study. Furthermore, Shillo and Halevy (1976b), Bastug et al (2006), andPereira et al (2009) mentioned that gladiolus vegetative development and flower stem initial growth are the most sensitive stages to soil water shortage.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…In addition, Wright and Burge (2000) observed that symptoms of water stress include lower growth, what is much apparent in this study. Furthermore, Shillo and Halevy (1976b), Bastug et al (2006), andPereira et al (2009) mentioned that gladiolus vegetative development and flower stem initial growth are the most sensitive stages to soil water shortage.…”
Section: Discussionsupporting
confidence: 69%
“…Spreng. ), Wright and Burge (2000) concluded that irrigation had no effects on flower stem number, but did increase flower size, as it also happened with the gladioli.…”
Section: Discussionmentioning
confidence: 99%
“…It is an important disease in Zantedeschia spp. and the major disease in cultivars of the section Aestivae (Kuehny, 2000;Wright and Burge, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Bacteria are spread mechanically during cultivation and symptoms can become visible during all stages of plant growth and development. Conditions are favourable for soft rot when plants are under stress during low soil aeration, high temperature or high relative humidity (Funnell and MacKay, 1999;Wright and Burge, 2000). Cultural measures such as drainage, mulching, soil ventilation and time of tuber lifting can reduce disease development (Funnell, 1993;Wright and Burge, 2000;Wright et al, 2002), but better control of the disease could be achieved by the use of resistant cultivars.…”
Section: Introductionmentioning
confidence: 99%
“…Welsh (1988) stated that soil and media should remain moist until the latter stages of the growing cycle of the calla plant. Wright & Burge (2000) reported that soil-grown callas in the field that were regularly irrigated had greater flower and tuber yields than callas that received water from rainfall only, and that the application of sawdust mulch to irrigated soil beds reduced the incidence of plant and tuber soft rots.…”
Section: Introductionmentioning
confidence: 99%